Robotic Resection of Pulmonary Epithelial Myoepithelial Carcinoma: A Case Report - Jindani, Rajika; Lopez, Michael A.; Miquel, Tatiana P.; Sylvin, Erik (The Thoracic and Cardiovascular Surgeon Reports, 2021)
Background Pulmonary epithelial–myoepithelial carcinoma (P-EMC) is an extremely rare, well-differentiated, and malignant neoplasm originating from submucosal bronchial glands in the lung. EMCs arise mainly in the salivary glands.Case Description This case represents an asymptomatic 78-year-old male with a remote 75-pack-year history of smoking who presents with a solitary endobronchial lesion, which is suggestive of a primary lung EMC, detected on annual screening chest computed tomography (CT) scan.Conclusion A recent review of literature reveals less than 50 documented cases of the pulmonary subtype of this tumor worldwide. We are reporting a unique case of robot-assisted pulmonary lobectomy for a P-EMC.
Keywords: pulmonary epithelial–myoepithelial carcinoma; robotic resection; salivary gland